Diabetic Foot and Leg Ulcer & Peri-wound Neuropathy Healing Feasibility Studies - Margaret, Kalmeta (Journal of Tissue Repair and Regeneration, 2026)
Diabetic foot and leg ulcers represent a significant global health burden and are frequently associated with peripheral neuropathy, vascular compromise, infection, and high rates of recurrence and amputation. Standard wound care often fails to achieve healing in chronic cases due to unaddressed underlying neuropathic and vascular pathology. This feasibility study evaluated the Hemastyl™ System in patients with long-standing diabetic foot and leg ulcers that had failed standard care and, in many cases, had been diagnosed for amputation. Two prospective feasibility cohorts comprising 39 chronic infected diabetic wounds were treated with the Hemastyl™ System. Outcomes included rapid microbe reduction, high wound closure rates, subjective improvement in neuropathy-related symptoms, and avoidance of amputation in all amputation-diagnosed cases. These findings suggest that targeting neuropathy, vasculature, and microbial burden concurrently may offer a promising approach for healing complex chronic wounds in high-risk populations.
Keywords: diabetic foot ulcers; chronic wounds; periwound neuropathy; feasibility study; wound closure; amputation prevention; Hemastyl™